1636: calabar's war ebook - Gannon, Charles E. (Ring of Fire, 2021)
NEW ENTRY IN THE BEST-SELLING RING OF FIRE SERIES FROM NEBULA AND DRAGON AWARD NOMINEE CHARLES E. GANNON AND ROBERT WATERS Domingos Fernandes Calabar started out as a military advisor for the Portuguese in Brazil. But to his superiors, he was still nothing more than a mameluco , a man of mixed blood. Until, that is, the Dutch arrived and he switched sides. Then the Portuguese had a new label for him: "traitorous dog." But when Dutch admiral Maarten Tromp arrives, having barely survived the disastrous Battle of Dunkirk, Calabar's job changes again. Now he has to help engineer a swift Dutch exodus to a safer place before word of Tromp's defeat reaches Spanish ears. Partnered with the Sephardic pirate Moses Cohen Henriques, the two aid the battered Dutch fleet by striking at the Portuguese and Spanish, both on land and sea. Until, that is, Calabar learns that bitter personal enemies have grabbed his family, put them in chains, and sold them to a slaveship bound for the Spanish Main. Calabar must now choose: continue to help the Dutch, or save his wife and children? Tromp and other strong allies want to put an end to slavery, too, but their strategies and timetable are measured in months and years. Calabar doesn't have that kind of time and can't rely on their methods. The struggle to recover his family, and to free the millions more suffering in shackles, is one he must win in his own way and on his own terms. Because ultimately, this is not just Calabar's fight. This is Calabar's war . At the publisher's request, this title is sold without DRM (Digital Rights Management).